APLIKASI TEKNIK AIRLIFT DIFFUSER PADA PENDEDERAN LOBSTER (Panulirus Sp) - Eko Efendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2023)
With the issuance of Ministerial Regulation of the Ministry of Fisheries Number 56 of 2016 concerning catching lobsters, crabs and blue swimming crabs, it can encourage the development of lobster farming businesses. The main problem in lobster nursery activities (Panulirus spp) is still having problems, namely the low survival rate at the juvenile lobster stage. This is presumably due to water quality, especially the low oxygen demand. Another factor is the cannibalistic nature of the juvenile lobsters. This service activity aims to provide understanding to the community, especially lobster collectors in Rangai Tri Tunggal Village, Katibung District regarding the application of airlift technology in lobster hatchery activities. In general, the level of knowledge and skills of group members regarding the manufacture of airlift diffusers is still low, namely 10%. However, after the training was held, knowledge and skills increased to 75%. Airlift diffuser technology is very appropriate to be used to help overcome production costs by reducing the use of electrical energy to assist in maintaining and managing water quality. Lobster cultivation can be used as a community business on a small scale and can be used as an alternative when there are restrictions on lobsters with sizes below those specified in KP Ministerial Decree No. 56 of 2016.